The components of an ontology-managed decision making - Чаплінський, Ю. П.; Надточій, В. І. (Problems of Informatization and Control, 2012)
The urgency of using ontologies to describe protsesa decision-making. The paper defined the structure of representation of decision-making. Rssmotreno multiple ontologies that implement a description of the tasks and decision-making processes of their solutions. The main characteristics of the components ontology-managed decision making